Absence of spermatozoal CD46 protein expression and associated rapid acrosome reaction rate in striped field mice (Apodemus agrarius) - Flanagan Brian F; Bryja Josef; Stopka Pavel; Frolikova Michaela; Andrlikova Petra; Clift Leanne E; Johnson Peter M; Dvorakova-Hortova Katerina (BMC, 2009)
Abstract Background In rodents, the cell surface complement regulatory protein CD46 is expressed solely on the spermatozoal acrosome membrane. Ablation of the CD46 gene is associated with a faster acrosome reaction. Sperm from Apodemus flavicollis (yellow-necked field mice), A. microps (pygmy field mice) and A. sylvaticus (European wood mice) fail to express CD46 protein and exhibit a more rapid acrosome reaction rate than Mus (house mice) or BALB/c mice. A. agrarius (striped field mice) belong to a different Apodemus subgenus and have pronounced promiscuity and large relative testis size. The aim of this study was to determine whether A. agrarius sperm fail to express CD46 protein and, if so, whether A. agrarius have a faster acrosome reaction than Mus. Methods Reverse transcription polymerase chain reaction (RT-PCR) was used to assess whether A. agrarius transcribe testicular CD46 mRNA. RT-PCR was supplemented with 3'- and 5'-rapid amplification of cDNA ends to determine the complete nucleotide sequence of A. agrarius CD46. Fluorescence microscopy was used to assess whether CD46 protein is expressed by A. agrarius sperm. The acrosome status of A. agrarius sperm was calculated over time by immunocytochemistry using peanut agglutinin lectin. Results We demonstrate that A. agrarius mice transcribe two unique alternatively spliced testicular CD46 mRNA transcripts, both lacking exon 7, which differ from those described previously in other Apodemus species. The larger A. agrarius CD46 transcript has an insert between exons 10 and 11 which, if translated, would result in a novel cytoplasmic tail. In addition, A. agrarius CD46 transcripts have an extended AU-rich 3'-untranslated region (UTR) and a truncated 5'-UTR, resulting in failure to express spermatozoal CD46 protein. We show that A. agrarius has a significantly faster spontaneous acrosome reaction rate than A. sylvaticus and Mus. Conclusion Absence of CD46 protein expression is associated with acrosomal instability in rodents. A. agrarius mice express novel CD46 transcripts, resulting in the trade of spermatozoal CD46 protein expression for a rapid acrosome reaction rate, in common with other species of field mice. This provides a strategy to increase competitive sperm advantage for individuals, leading to faster fertilisation in this highly promiscuous genus.